2021
DOI: 10.1126/sciimmunol.abg2329
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells promote innate inflammation after skin barrier breach via TGF-β activation

Abstract: Regulatory T cells (Tregs) use multiple mechanisms to attenuate inflammation and prevent autoimmunity. Tregs residing in peripheral (i.e., nonlymphoid) tissues have specialized functions; specifically, skin Tregs promote wound healing, suppress dermal fibrosis, facilitate epidermal regeneration, and augment hair follicle cycling. Here, we demonstrated that skin Tregs were transcriptionally attuned to interact with their tissue environment through increased expression of integrin and TGF-β pathway genes that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
1
29
0
1
Order By: Relevance
“…Tregs in soft tissue have also been found to enhance the regenerative process, mainly by enforcing immune tolerance and suppressing excessive inflammation [ 194 ]. For instance, Moreau et al [ 195 ] have reported that Treg-derived amphiregulin induces tissue-resident T cell proliferation upon injury, thus leading to an immune-suppressive microenvironment and tissue regeneration (Fig. 2 a).…”
Section: Immune Microenvironment In Tissue Regenerationmentioning
confidence: 99%
“…Tregs in soft tissue have also been found to enhance the regenerative process, mainly by enforcing immune tolerance and suppressing excessive inflammation [ 194 ]. For instance, Moreau et al [ 195 ] have reported that Treg-derived amphiregulin induces tissue-resident T cell proliferation upon injury, thus leading to an immune-suppressive microenvironment and tissue regeneration (Fig. 2 a).…”
Section: Immune Microenvironment In Tissue Regenerationmentioning
confidence: 99%
“…Recent evidence adds new examples and mechanisms. Regulatory T (Treg) cells are indispensable for resolution of inflammation ( Hu et al., 2021 ), yet intradermal Treg cells promoted epidermal inflammation in wounded skin by driving keratinocytes to produce neutrophil-recruiting chemokines ( Moreau et al., 2021 ). Platelets helped resolve the pulmonary inflammation associated with bacterial pneumonia in mice by physically trapping Treg cells in the lung and inducing a pro-resolution transcriptional program in macrophages ( Rossaint et al., 2021 ).…”
Section: Anti-inflammatory Functions Of Pro-inflammatory Cellsmentioning
confidence: 99%
“…CellPhoneDB analysis of mouse scRNA-seq data predicted ephrin signaling-mediated epithelial-mesenchymal crosstalk that enables mesenchymal competence for regeneration in skin wound healing[ 55 ]. Another application of CellPhoneDB to skin injury revealed that αvβ8 expression in skin Tregs helps to activate TGF-β in neighboring keratinocytes, which act directly on epithelial cells to promote CXCL5 production and neutrophil recruitment, suggesting that αvβ8-expressing Tregs contributes to innate inflammation and delayed epidermal repair after inducing skin injury [ 56 ]. In addition, NicheNet analysis was applied to identify the signals driving the response of OTULIN-deficient keratinocytes to inflammation [ 57 ].…”
Section: Biological Insights Gained By Cell–cell Communication Analys...mentioning
confidence: 99%